LEGAL PROTECTION FOR CUSTOMERS IN MURABAHAH TRANSACTIONS WITHIN ISLAMIC BANKING - Choliza, Tia; Zakiruddin, Muhammad Aziz (Institut Agama Islam Negeri Metro, 2025)
The rapid development of Islamic banking in Indonesia reflects the increasing public demand for financial services that comply with sharia principles. Among the most widely used financing instruments is the murabahah contract, a cost-plus sale agreement practiced by Islamic financial institutions. Although conceptually simple, the implementation of murabahah in banking frequently encounters legal and practical challenges that may reduce the effectiveness of customer protection. This research analyzes the legal protection mechanisms embedded in murabahah financing as regulated in Islamic law, the Sharia Banking Act, and DSN-MUI Fatwas. Using a normative juridical approach supported by statutory analysis and conceptual interpretation, the study examines how murabahah regulates asymmetric contractual relations in which banks possess superior information, technical capacity, and bargaining power compared to customers. The findings indicate that, in practice, several aspects of murabahah—such as transparency of cost and margin, ownership transfer, risk allocation, and default handling—do not always align with sharia principles and consumer protection standards. Strengthening regulatory enforcement, improving contract literacy, and ensuring compliance with sharia governance are essential to optimize legal protection for customers in murabahah transactions. This study contributes to the discourse on sharia-compliant financing by offering a comprehensive evaluation of existing legal frameworks and their practical implications.